Collective wisdom : lessons, inspiration, and advice from women over 50 - Bonney, Grace (Artisan, a division of Workman Publishing Co., Inc., 2021)
"In her new book, Grace Bonney continues where In the Company of Women left off and connects the dots between women of all generations (from ages 18 to 100), offering a brand-new perspective on empowering and empowered women. Collective Wisdom will include a multilayered tapestry of interviews, conversations, intimate photos, wish lists, artwork, images of handwritten letters, and more, designed so it's both a keepsake and a treasury of wisdom that readers will turn to often and gift to others. Collective Wisdom will celebrate all the different ways women form community and how those relationships keep us going in trying times. Over 70 percent of the book will feature women of color, women with disabilities, and women from the LGBTQ+ community"--